Private Peaceful - Morpurgo, Michael (London HarperCollins Children Books, 2003)
The Peaceful brothers, Tommo and Charlie, have a tough rural childhood facing the death of their father, financial hardship and a cruel landlord. Their fierce loyalty to each other pulls them through, until one day they both fall for the same girl. And then the Great War comes. The play tells the story of a country lad fighting a war he doesn$1 (Bt understand for people he cannot respect. We join 18-year-old Private Tommo Peaceful in the trenches as he tells us a story of courage, devotion and sibling rivalry on what may be his last night on earth. Private Peaceful was shortlisted for the Carnegie Medal, won the Red House Children$1 (Bs Book Award and the Blue Peter Book Award and is acknowledged by Michael Morpurgo (War Horse, The Butterfly Lion) to be his favorite work. This small ensemble version by Simon Reade was commissioned by Nottingham Playhouse.-- Provided by publishers
Illustration
Keywords: People with mental disabilities -- Single-parent families -- Children